1998
DOI: 10.1002/(sici)1097-0193(1998)6:4<216::aid-hbm3>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dynamics of attention to color: Evidence from human electrophysiology

Abstract: This study characterized patterns of brain electrical activity associated with selective attention to the color of a stimulus. Multichannel recordings of event-related potentials (ERPs) were obtained while subjects viewed randomized sequences of checkerboards consisting of isoluminant red or blue checks superimposed on a grey background. Stimuli were presented foveally at a rapid rate, and subjects were required to attend to the red or blue checks in separate blocks of trials and to press a button each time th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
146
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(176 citation statements)
references
References 74 publications
26
146
2
Order By: Relevance
“…Previous ERP studies on feature selection have typically found the earliest modulations of stimulus processing in the form of a selection negativity beginning around 170 ms post stimulus onset (cf 26,27). In these cases, the tobe-attended color was known before stimulus onset; i.e., these times supposedly do not involve the time required to interpret the cue and to shift attention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ERP studies on feature selection have typically found the earliest modulations of stimulus processing in the form of a selection negativity beginning around 170 ms post stimulus onset (cf 26,27). In these cases, the tobe-attended color was known before stimulus onset; i.e., these times supposedly do not involve the time required to interpret the cue and to shift attention.…”
Section: Discussionmentioning
confidence: 99%
“…A repetitive pulse-train of TMS was delivered on each trial, from 100 to 500 ms after cue onset (five pulses at 10 Hz). The timing of this pulse train was selected to encompass the most likely period during which the parietal cortex would be necessary for controlling spatial and feature-based attention (Anllo-Vento et al, 1998;Slagter et al, 2005a,b). The intensity of stimulation was delivered randomly on a trial-by-trial basis at 40% (low) or 120% (high) of individual resting motor threshold.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown extensively that selective attention can be deployed to spatial locations (Posner, 1980), objects or their features (Anllo-Vento, Luck, & Hillyard, 1998;Duncan, 1984), motor action (Rushworth, Krams, & Passingham, 2001), temporal intervals (Coull & Nobre, 1998), or information held in working memory (Griffin & Nobre, 2003). One of the most interesting aspects of attentional selection is its temporal profile, as it is informative about the stages of information processing (early vs. late) that are affected by the deployment of attention.…”
Section: Introductionmentioning
confidence: 99%